Study Teaching English to Tunagrahita Student Through Picture Card: English - Ukhtul Iffah; Nuril Firdaus; Hanin Aisyah (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
Education isn’t just about normal kids. Education for Tunagrahita child also important for their life. because we don’t know if their skills can make them successful and can follow the competition internationally. Many kinds of rehabilitation children are called these special needs children. Tunagrahita is a child who has a standard IQ of 40-70. A disabled child with a bell-average IQ is very difficult to receive a lesson with a fast explanation. The teachers for the disabled child have to repeat several times the explanations to the child with low IQ The research is to find out the good method and be provided good learning services to the literacy of Tunagrahita’s children. The purpose of this research is to find out good methods for English lessons for Tunagrahita students and provided good learning services to the literacy of Tunagrahita’s children. The research method in this research is qualitative method with the data collection of research observation, interview, and documentation. In this research, the subject is the chief of SLBN 1 Jembrana, some teachers, staff also students. And for data analysis, the researcher used qualitative descriptive. From this research, the researcher concluded some findings, that: a) with picture cards and practice Tunagrahita students easier learn English literacy. b) Tunagrahita students difficult to understand something. So, the teacher of tunagrahita students must stimulate tunagrahita thinking before starting the lesson. c) Tunagrahita students are interested in something unique. So, teachers must be creative in giving subjects to them.